2019 Kenya Population and Housing Census Volume IV: Distribution of Population by Socio-Economic Characteristics - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)

Kenya Population and Housing Census Results - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)
The total enumerated population was 47,564,296 Of which 23,548,056 were Males, 24,014,716 were Females and 1,524 were Intersex Females accounted for 50.5% of the total population The population has grown to 47.6 Million in 2019 from 37.7 Million in 2009 The intercensal growth rate has declined to 2.2% in 2019, from 2.9% in 2009 Average …